PRESCRIBING ANTIBIOTICS USING WHO PRESCRIBING INDICATORS AMONG OUTPATIENTS IN HEALTH SERVICES IN KABUL, AFGHANISTAN: A CROSS-SECTIONAL STUDY, 2024 - Rahmatullah Nazari; Mohammad Firdous Wahid; Abdullah Faizzad; Asadullah Danishyar; Ishaq Panahi; Don Eliseo Lucero-Prisono (Scholar Express Journals, 2025)
Antibiotics are essential for treating bacterial infections and are among the most commonly prescribed drugs worldwide. However, their inappropriate use has led to a global increase in antimicrobial resistance (AMR), particularly in low- and middle-income countries. The World Health Organization (WHO) has developed prescribing indicators to monitor and promote rational medicine use. In Afghanistan, data on antibiotic prescription patterns, especially in outpatient settings, remain limited and fragmented, raising concerns about high prescription rates and nonadherence to standard protocols. A systematic evaluation using WHO indicators is crucial for informing healthcare practices and combating AMR
Keywords: WHO prescribing indicators; Antibiotic; Kabul